Perbandingan Hasil Investasi BPJS Ketenagakerjaan dalam Pengelolaan Dana Pensiun - Henrianto M.Ec.Dev; Tanti Novianti (Jurnal Pasar Modal dan Bisnis, 2022)
The total investment of BPJS Ketenagakerjaan (agency) was recorded at Rp. 11,656 billion, the dominant investment portfolios were bonds, stocks, time deposits, sukuk and mutual funds. The purpose of this study is to compare financial instruments as a forum for BPJS Employment in allocating funds for the development of Pension Security so that it is expected to provide high returns. This type of research is a qualitative research with the method used is a descriptive method of content analysis, namely comparing the returns generated by each of the 3 (three) variables, namely stocks, bonds and deposits. The results of this study indicate that of the three financial instruments that provide the highest return, bonds are Rp. 6,614,426,103,588, - or about 26.16%. Next is the stock market financial instrument that provides a return of Rp. 6,207,042,474,170,- or about 24.55%. Lastly, investing by saving funds in state-owned banks that provide deposit interest every year amounting to IDR 5,413,654,515,898, - or around 21.41%. So it can be concluded that the right choice to provide the highest portion in the allocation of BPJS Employment pension funds in investment is bonds.